Relative power and efficiency as a main determinant of banks’ profitability in Latin America - Guillén, Jorge (2014)
Despite the financial sector liberalization and openness that started in the earlier 90's and significant macroeconomic development as well as increasing inflow of capital toward the region, there is not any evidence of the reduction of interest rates as well as banks' profits in Latin America. In this paper we develop a model to estimate the determinants of Latin American banks' profitability and, try to understand the reasons why banks are reluctant to decrease their interest rate spreads even when change in competitiveness in the financial system is improving. By using Data Envelopment Analysis to better exploit the information of several variables at the same time and, by employing a sample of 200 Banks located in Argentina, Bolivia, Brazil, Costa Rica, Ecuador, El Salvador, Mexico, Nicaragua, Paraguay, Peru, Uruguay and Venezuela; we find that banks' profits grew consistently above the normal levels of profits adjusted by risk. Our results show that banks in Latin America have been profiting from their oligopolistic position in detriment of their clients in particular and of their whole economy in general.